Nonlinear coupled dynamic modelling of driver-seat-cab system and biomechanical behaviour prediction - Zhao, Leilei (Strojniški vestnik, 2022)
The biomechanical responses of the driver-truck system in a dynamic environment have become a significant concern in the design and control of trucks. When evaluating the riding comfort of the seat-cab system, it is necessary to predict the biomechanical responses of the driver’s different parts and directions. However, there is no reliable model and method for effectively predicting the response characteristics of the driver-seat-cab system. Aiming at such problem, firstly, based on the 7 DOF (degree-of-freedom) seated human biodynamic model established previously, a 10 DOF non-linear dynamic model of the driver-seat-cab system was created, and its vibration differential equations were established. Secondly, the vibration signals for simulation and verification were collected through the road test using a truck. Thirdly, based on the Newmark-ß integration method, the specific solution process of the model was given. The non-linear damping coefficients of the front and rear dampers for the cab suspensions were measured with a bench test. Moreover, the simulations were conducted based on the measured model parameters, taking the collected frame vibration signals as the inputs. The results show that the simulation results agree with the test results, proving that the dynamic model can effectively predict the driver’s biomechanical responses. Finally, some useful conclusions were obtained through the simulation analysis. The established model and conclusions can provide technical support for comfort evaluation, optimization design, and control of the seat-cab suspension system.
Keywords: avtomobilska tehnika; biomechanical responses; biomehanski odziv; dinamično modeliranje; driver’s health; driver-seat-cab system; dynamic modeling; kakovost vožnje; sistem voznik-sedež-kabina; voznikovo zdravje